The Role of Al-‘Afw in Mitigating the Culture of Public Punishment (Cancel Culture) a Contextual Study of At-Tabari’s Interpretation of QS. Ali-Imran: 134: Konsep al-‘afw dalam Meredam Budaya Hukuman Publik (Cancel Culture): Kajian Kontekstual atas Tafsir at-Ṭabari terhadap QS. Ali ‘Imran [3]: 134 - Hafiz Hafiz; Jenni Mita Sari; Akbar Rakhman Hidayat (Takwil: Journal of Quran and Hadith Studies, 2025)
This article aims to explore the role of Al-Afw in mitigating cancel culture. in the perspective of At-Tabari's interpretation of QS. Ali-Imran: 134, focusing on the verse by offering an ethical response to the practice of cancel culture. This study uses a qualitative method through library research on the text of the Qur'an, At-Tabari's interpretation of Jami' al-Bayan, and contemporary scientific literature on cancel culture. The results of the study indicate that cancel culture can cause social problems in the form of ostracism and public punishment that are often carried out without providing space for clarification and forgiveness. Therefore, mitigation of cancel culture can be done by prioritizing the value of forgiveness that opens up space for social reconciliation, avoiding intolerant attitudes, and building harmony and civilized social justice. In this context, Islamic teachings through QS. Ali-Imran: 134, as interpreted by At-Tabari, emphasize the importance of the value of forgiveness (Al-'Afin) and restraining anger as an attitude to reduce destructive cancel culture. This study emphasizes the importance of building a culture of forgiveness in modern digital society to create a more just, empathetic, and civilized social harmony. At-Tabari's interpretation provides a strong foundation for formulating Islamic public ethics that are able to respond to contemporary moral challenges in a wiser and more humane manner